2022
DOI: 10.3389/fmed.2022.901817
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Infection, Predictors of Severe Disease, and Antibody Response to COVID-19 in Patients With Inflammatory Rheumatic Diseases in Portugal—A Multicenter, Nationwide Study

Abstract: ObjectiveTo identify risk factors for SARS-CoV-2 infection and for severe/critical COVID-19, and to assess the humoral response after COVID-19 in these patients.MethodsNationwide study of adult patients with inflammatory RMDs prospectively followed in the Rheumatic Diseases Portuguese Register—Reuma.pt—during the first 6 months of the pandemic. We compared patients with COVID-19 with those who did not develop the disease and patients with mild/moderate disease with those exhibiting severe/critical COVID-19. Ig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Rheumatic disease patients were thought by some to be at higher risk of contracting COVID-19 and having worse outcomes, once infected 9 whereas others denied it. 10 Albeit true for some rheumatic diseases, in most of these syndromes poor outcomes may be pertinent to the severity of disease and other disease-specific or general factors rather than the diagnosis itself. The current study explored the influence of rheumatic disease activity on COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatic disease patients were thought by some to be at higher risk of contracting COVID-19 and having worse outcomes, once infected 9 whereas others denied it. 10 Albeit true for some rheumatic diseases, in most of these syndromes poor outcomes may be pertinent to the severity of disease and other disease-specific or general factors rather than the diagnosis itself. The current study explored the influence of rheumatic disease activity on COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8 A study suggested that those with moderate disease activity (MDA) or high disease activity (HDA) had poorer outcomes 9 whereas some studies did not find any such relationship. 10 A Danish study observed that the risk of hospitalisation with COVID-19 was 46% higher for people with rheumatic disease than for the general population, but after adjustment for age, gender and comorbidities, only people with RA still had an increased risk of a poor outcome. 11 The current study was planned to conduct a multi-centre study in Pakistan to see the effect of disease activity state of various rheumatic diseases on COVID-19-related outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In line with other studies, we found an association between patients with COVID-19 requiring hospitalization and arterial hypertension (p = 0.01) 2 and age (p = 0.013). 5 Gout (p = 0.01) and vaccination status (p = 0.05) were also associated with a worse prognosis. In the multivariate analysis, only older patients […”
mentioning
confidence: 97%